(untitled) (International journal of artificial intelligence, 2026)
This article investigates the artistic and figurative devices employed in the literary works of Mark Twain and Khudoyberdi Tokhtaboyev. The study focuses on stylistic elements such as metaphor, irony, hyperbole, symbolism, and personification, examining their role in shaping narrative structure, enhancing aesthetic value, and conveying ideological meaning. Through a comparative literary analysis, the article demonstrates how both authors utilize figurative language to reflect social realities, develop characters, and engage readers. Despite differences in cultural and historical contexts, Twain and Tokhtaboyev share a common artistic approach in their effective use of figurative devices to combine humor, criticism, and moral reflection.